DECENTRALIZED APPLICATION FOR AUTO-INSURANCE INDUSTRY: AN INTERPLANETARY FILE SYSTEM AND BLOCKCHAIN-BASED PARADIGM FOR OPTIMAL DATA AND CLAIM MANAGEMENT - Muhammad Hannan Tariq; Majid Hussain; Samraiz Zahid; Rana Hassam Ahmed (International Journal of Contemporary Issues in Social Sciences, 2024)
The auto-insurance industry faces significant challenges related to data security, fraud, and inefficiencies due to its centralized structure, reliance on intermediaries, and extensive paperwork. These issues compromise trust and transparency, key elements for effective insurance management. This paper proposes a solution that leverages blockchain technology and the Interplanetary File System (IPFS) to create a decentralized, secure, and transparent platform for managing policy and claim data. The system uses Ethereum-based smart contracts and IPFS to enhance the efficiency and security of auto-insurance processes. A multi-consensus mechanism ensures all stakeholders, including insurers and policyholders, participate equitably in claim approvals and settlements, reducing the need for intermediaries and improving trust.A notable feature is the vehicle lifecycle management module, which securely tracks vehicle data throughout its lifespan, reducing fraud and streamlining processes. The Decentralized Application (DApp) interface allows users to create policies, submit claims, and track their progress in real time, with data securely stored on IPFS to ensure immutability and decentralization.By combining blockchain’s consensus and security strengths with IPFS’s scalable storage, this solution aims to enhance transparency, reduce fraud, and improve operational efficiency in the auto-insurance industry.